A lesson for site-selective C-H functionalization on 2-pyridones: radical, organometallic, directing group and steric controls - Hirano, Koji; Miura, Masahiro (Chemical science (Cambridge), 2018)
A 2-pyridone ring is a frequently occurring subunit in natural products, biologically active compounds, and pharmaceutical targets. Thus, the selective synthesis of substituted 2-pyridone derivatives through decoration and/or formation of pyridone rings has been one of the important longstanding subjects in organic synthetic chemistry. This minireview focuses on recent advances in site-selective C-H functionalization on 2-pyridone. The reported procedures are categorized according to the site selectivity that is achieved, and the substrate scope, limitations, mechanism, and controlling factors are briefly summarized. This minireview focuses on recent advances in site-selective C-H functionalization on 2-pyridone which is an important heterocyclic motif in medicinal and pharmaceutical chemistry.